Psychopathic personality disorder : capturing an elusive concept - Cooke, David J. (Array, 2018)
The diagnosis of psychopathic personality disorder has salience for forensic clinical practice. It influences decisions regarding risk, treatability and sentencing, indeed, in certain jurisdictions it serves as an aggravating factor that increases the likelihood of a capital sentence. The concatenation of symptom that is associated with modern conceptions of the disorder can be discerned in early writings, including the book of Psalms. Despite its forensic clinical importance and historical pedigree the concept remains elusive and controverted. In this paper I describe an attempt to map the concept of psychopathic personality disorder—the Comprehensive Assessment of Psychopathic Personality (CAPP). I outline the processes used to create the concept map; I summarise evidence in support of the content validity of the map and describe different operations designed to operationalise the construct. It is only when conceptual clarity is achieved that valid operations and measures can be created. I end with a plea for more carefully considered application of statistical methods; applications that better fit the theoretical questions being posed.